2021
DOI: 10.1186/s13075-021-02466-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of glucocorticoid doses and emotional health in lupus low disease activity state (LLDAS): a cross-sectional study

Abstract: Background While survival of systemic lupus erythematosus (SLE) patients has improved substantially, problems remain in the management of their emotional health. Medium to high-dose glucocorticoid doses are known to worsen emotional health; the effect is unclear among patients receiving relatively low-dose glucocorticoids. This study aims to investigate the association between low glucocorticoid doses and emotional health in lupus low disease activity state (LLDAS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…And the number of SLE symptoms significantly contributed to the quality of life which was consistent with previous study. 29 In agreement with previous study (Ratanasiripong et al), skin manifestations (skin rash alopecia and mucosal ulcers) were the most common symptom among participants, and randomized controlled trials have shown that using cosmetics can mask rashes and improve depression, anxiety and quality of life scores. 30 , 31 Meanwhile, patients with skin involvement also had higher likelihood of having coexisting anxiety and depression.…”
Section: Discussionsupporting
confidence: 90%
“…And the number of SLE symptoms significantly contributed to the quality of life which was consistent with previous study. 29 In agreement with previous study (Ratanasiripong et al), skin manifestations (skin rash alopecia and mucosal ulcers) were the most common symptom among participants, and randomized controlled trials have shown that using cosmetics can mask rashes and improve depression, anxiety and quality of life scores. 30 , 31 Meanwhile, patients with skin involvement also had higher likelihood of having coexisting anxiety and depression.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, we found no reduction in mental disorders within patients who attained a state of low-lupus activity. Subgroup analysis according to intake or not of glucocorticoids yielded similar findings, thus reducing the possibility for a treatment confounding effect [ 57 ]. Our results are in agreement with a longitudinal study of 139 SLE patients which revealed four distinct anxiety trajectories that remained stable and not affected by disease activity over an average period of 30.9 months [ 58 ].…”
Section: Discussionmentioning
confidence: 93%
“…QoL, but also in other aspects such as adherence to treatment and self-management of the disease (Dima et al, 2019;Miyawaki et al, 2021;Porta et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although effective, the use of glucocorticoids has been related with neuropsychiatric manifestations, such as depression and anxiety, previous studies have observed an inverse association between glucocorticoid dose and emotional health. It is also important to highlight that some of the side effects of their use, besides potential organ damage, are weight gain and other appearance-related effects, which can contribute to self-perception and mental health (Miyawaki et al, 2021; Porta et al, 2020). The sum of all these factors, in addition to physical limiting manifestations such as arthritis or lupus headache, influence the self-perception that the patient has over her health and QoL; which explain why self-perception of health and quality of life are the main variables contributing to QoL in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation